The Metabolic Syndrome: Comparison of Newly Proposed IDF, Modified ATP III and WHO Criteria and their Agreements (Cardiovascular Journal, 2013)
Background: Metabolic syndrome (MS) results from clustering of cardiovascular risk factors occurring in association with insulin resistance and obesity. With the increasing prevalence of obesity worldwide, MS is of keen interest in research. The disorder is defined in various ways, but one consolidated definition is needed to make studies comparable worldwide. The study was to determine the risk factors of metabolic syndrome in Bangladesh and comparison of newly proposed definition of International Diabetes Federation (IDF), modified National Cholesterol Education Program Adult Treatment Panel III (NCEP ATP III) and the World Health Organization (WHO) criteria and their agreements. Materials and Methods: This was a cross sectional hospital based study. We randomly selected 229 participants. After obtaining informed written consent data collectors collected data by interview, clinical examination, anthropometric measurement and investigations. We calculated independent sample t-test means between to distinguish which risk factors were present in participants with and without MS, using SPSS v17. Results: The percentage of risk factors of MS among subjects according to different criteria was 72% of Modified ATP-III, 69% of IDF and 39% of WHO definition .In Modified NCEP ATP III when did independent sample t-test mean of BMI, waist circumference, systolic blood pressure, diastolic blood pressure, fasting blood glucose, high density lipoprotein and triglyceride were present statistically significant difference between without MS and with MS (p